2016
DOI: 10.1109/tdei.2015.005234
|View full text |Cite
|
Sign up to set email alerts
|

An OH-PDMS-modified nano-silica/carbon hybrid coating for anti-icing of insulators part I: Fabrication and small-scale testing

Abstract: Super-hydrophobic coatings have recently drawn a lot of attention in research andapplications towards reduction of ice accumulation on insulators. This paper presents a new type of hybrid coating fabricated via self-assembly of a super-hydrophobic layer on a semi-conducting layer. Hydroxy-terminated polydimethylsiloxane (OH-PDMS) modified nano-silica is used for fabrication of the super-hydrophobic layer. Fabrication procedures, hydrophobic characteristics, and flashover performances of the hybrid coating are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…It is a better choice to apply the semiconductor coating on the lower surface and the outer edge of the upper surface of the insulator with a 5-8 cm exposed area. Li et al (2016) and Yan et al (2016) prepared carbon/nano-silica/ PDMS coatings with both semiconducting and superhydrophobic properties on insulators via dip coating and self-assembly techniques. The SEM image is shown in Figure 8A.…”
Section: Semiconductor Coatingsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a better choice to apply the semiconductor coating on the lower surface and the outer edge of the upper surface of the insulator with a 5-8 cm exposed area. Li et al (2016) and Yan et al (2016) prepared carbon/nano-silica/ PDMS coatings with both semiconducting and superhydrophobic properties on insulators via dip coating and self-assembly techniques. The SEM image is shown in Figure 8A.…”
Section: Semiconductor Coatingsmentioning
confidence: 99%
“…The SEM image of the carbon/nano-silica/PDMS coating (Li et al, 2016). (B) Typical leakage current waveforms of insulators with carbon/ nano-silica/PDMS coating (Yan et al, 2016).…”
Section: Figure 8 (A)mentioning
confidence: 99%
“…Recently, hydrophobic silicone rubbers have been fabricated using various methods, such as laser processing, surface coating, injection molding, and so on. 3,[12][13][14][15][16][17] As a basic approach to produce surface micro/nanostructures, laser processing is a useful technique in preparing superhydrophobic surfaces with a wide range of materials. [18][19][20] Although previous researches have demonstrated that the wettability of the silicone rubber can be tuned by a femtosecond laser, 21,22 the reliable dynamic superhydrophobic stability still needs to be taken into consideration for the application associated with industrial and practical applications, such as high voltage transmission lines.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, hydrophobic silicone rubbers have been fabricated using various methods, such as laser processing, surface coating, injection molding, and so on 3,12–17 . As a basic approach to produce surface micro/nanostructures, laser processing is a useful technique in preparing superhydrophobic surfaces with a wide range of materials 18–20 .…”
Section: Introductionmentioning
confidence: 99%